First Insight into the Prevalence of Coxiella burnetii Infection among Veterinary Medicine Students in Bulgaria - Petia Genova-Kalou; Yordan Hodzhev; Ilia Tsachev; Roman Pepovich; Stefan Panaiotov; Veselin Dobrinov; Stefka Krumova; Betina Boneva-Marutsova; Borislava Chakarova; Keytlin Todorova; Konstantin Simeonov; Magdalena Baymakova; et al. (MDPI AG, 2024)
The aim of this study was to assess the prevalence of Coxiella burnetii infection among veterinary medicine students from two Bulgarian Universities, located in Sofia and Stara Zagora. Blood samples were collected from a total of 185 veterinary students for the detection of C. burnetii phase II antibodies and presence of DNA using an enzyme-linked immunosorbent assay (ELISA) and end-point PCR test. Out of all samples, 29.7% were positive for at least one C. burnetii phase II antibody marker or by the result of the PCR test. Veterinary students from Stara Zagora showed a significantly high seropositivity for Q fever (33.6%), as compared to the students in Sofia (23%; p < 0.05). Evidence of recent exposure with detection of anti-C. burnetii phase II IgM (+) antibodies was observed in 14.6% of the students under study. Seroprevalence among students in Stara Zagora was higher (15.3%). Anti-C. burnetii phase II IgG antibodies were detected in 21.6% of examined samples. Our study revealed a higher seropositivity among the male students (32.8%) as compared to females (16.0%; p < 0.05). The end-point PCR assay detected 5.9% blood samples as positive. The relative risk (RR) of Q fever exposure for male students was 40.7%, whereas it was 24.6% in females (p < 0.05). The findings from this study indicate that the C. burnetii infection is widely distributed amongst veterinary students in Bulgaria. This study emphasizes the need for improved safety protocols and infection control measures in veterinary training programs.